Climate Controls on the Interseasonal and Interannual Variability of the Surface Mass and Energy Balances of a Tropical Glacier (Zongo Glacier, Bolivia, 16°S): New Insights From the Multi‐Year Application of a Distributed Energy Balance Model. Issue 7 (7th April 2022) - Autin, P.; Sicart, J. E.; Rabatel, A.; Soruco, A.; Hock, R.
Abstract: The application of a distributed energy balance model over nine years at an hourly time step to a 20 × 20 m grid cell over Glacier Zongo (Bolivia, 16°S) enabled assessment of the climate factors that control the interseasonal and interannual variability of its surface mass balance. The model was validated by comparing the measured and simulated discharge at the outlet, albedo at the Automatic Weather Station, surface state and annual mass balance both glacier‐wide and as a function of altitude. Analysis of the mean monthly energy fluxes highlighted the importance of the meteorological conditions over October and November on the variability of the annual surface mass balance. Two sensitivity analyses are presented, one of the distribution of precipitation over time which maintains a physical coherence between the different meteorological variables and one of the impact of prolonged periods of intense cloud radiative forcing on the surface mass balance. The distribution of precipitation events over time and their associated amounts are the main drivers of the interannual variability of the surface mass balance via an albedo feedback effect. Additionally, prolonged periods of negative cloud radiative forcing, specifically over the month of November, notably reduce the melt rate. Plain Language Summary: This study aimed at identifying the meteorological variables which control the seasonal and annual melt rates of a tropical glacier in Bolivia considering nine years of measurements at the hourly timescale. The analysis of the energy fluxes at the weather station has shown that the period between the austral winter and summer is the period during which most melt can be generated making it key in defining the annual melt rates. The analysis of the impact of measured meteorological variables on the melt rate has shown that it is the solar energy that controls most of it. The amount of solar energy available for melt is defined by the state of the glacier surface (snow, ice, debris) which controls the amount of reflected energy. In this context, the frequency of the snowfall events plays a key role in controlling the melt as frequent events imply a whiter glacier which is able to reflect most of the incoming solar energy. Similarly, because clouds can block large portions of solar energy, sustained cloud periods can play an important role in reducing the melt rate. Key Points: Seasons over Zongo Glacier can be identified using the distribution of the cloud radiative forcing October and November play a strong control on the interannual surface mass balance variability of Zongo Glacier Distribution of the precipitation events in time is key in controlling the melt rate